Reduction in wind force in relation to corner design of bridge piers - Štimac Grandić, Ivana (Array, 2020)
The effects of wind on beam bridges can be significantly reduced with careful design of deck, roadway and wind barriers, as well as with appropriate design of piers. In this paper, the influence of corner design of rectangular cross-sectional piers to total wind force on piers is investigated. The total wind force changes, due to a different corner design of rectangular cross section of piers in free standing phase, are analyzed for piers of different heights, different environments and different wind velocities. The correlation between changes in total wind force and changes in geometric properties of a pier is also shown. By rounding the corners of a pier square cross section, the total wind force on pier in free standing phase can be drastically reduced in comparison to the total wind force on sharp corner pier with a small reduction in a load bearing properties of the pier. Changes in the bridge pier environment, as well as changes in pier height and wind velocity have negligible influence on changes in reduction of total wind force due to rounding the pier corners.